PHA composition and method for producing same

The PHA composition, comprising 3HB and 4HB in a P3HB-4HB copolymer with specific molecular weight ranges, addresses the challenge of achieving improved adhesive and mechanical properties in biodegradable plastics, ensuring biodegradability and environmental sustainability without additional chemicals.

JP7670815B2Active Publication Date: 2025-04-30CJ CHEILJEDANG CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023519254
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-10-23
Filing Date
2021-10-21
Publication Date
2025-04-30
Estimated Expiration
2041-10-21

AI Technical Summary

Technical Problem

Existing biodegradable plastic compositions struggle to achieve both improved adhesive properties and mechanical properties, such as tensile strength and elongation, while maintaining biodegradability and avoiding the use of additional chemicals that can lead to environmental pollution.

Method used

A polyhydroxyalkanoic acid (PHA) composition comprising 3-hydroxybutyric acid (3HB) and 4-hydroxybutyric acid (4HB) in a poly-3-hydroxybutyric acid-co-4-hydroxybutyric acid (P3HB-4HB) copolymer, with a weight average molecular weight of 130,000 to 700,000 and a number average molecular weight of 60,000 to 350,000, which is mixed to achieve a weight ratio of 10:90 to 90:10, thereby enhancing adhesive and mechanical properties without the need for additional chemicals.

Benefits of technology

The PHA composition achieves adhesive strengths of 1 kg/in or more, tensile strengths of 0.1 Mpa or more, and elongation rates of 200% or more, making it suitable for use as a sealant while maintaining biodegradability and environmental friendliness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007670815000001
    Figure 0007670815000001
Patent Text Reader

Abstract

The present invention relates to a biodegradable plastic polyhydroxyalkanoate (PHA) composition with improved adhesive and mechanical properties, and a method for producing the same. Specifically, the present invention provides a composition that has excellent adhesive properties with plastic materials by improving adhesive properties using only biodegradable PHA without the need for additional chemicals. Furthermore, the present invention provides a composition that has improved not only adhesive properties but also mechanical properties. Therefore, the composition can be easily applied to products that require a good balance between biodegradability, adhesive properties, and mechanical properties, allowing for the production of environmentally friendly products that are harmless to the human body.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to biodegradable plastic polyhydroxyalkanoate (PHA) compositions having improved adhesive and mechanical properties and methods for their preparation.

[0002] This application claims the benefit of priority based on Korean Patent Application No. 10-2020-0137921, filed on October 23, 2020, and all contents disclosed in the documents of the Korean Patent Application are incorporated herein by reference. [Background technology]

[0003] Polyhydroxyalkanoates (PHAs) are biodegradable plastics that are used, without limitation, in the manufacture of films (e.g., packaging films, agricultural films, mulch films), golf tees, caps and closures, agricultural supports and stakes, paper and board coatings (e.g., cups, plates, boxes, etc.), thermoformed products (e.g., trays, containers, yogurt pots, flower pots, noodle bowls, molded products, etc.), housings (e.g., for electronic products), bags (e.g., garbage bags, sundries bags, food bags, fertilizer bags, etc.), hygiene products (e.g., diapers, feminine hygiene products, urinary incontinence products, disposable wipes, etc.), and coatings for granular products (e.g., granular fertilizer, herbicides, insecticides, seeds, etc.).

[0004] PHAs are also used in the development of biomedical devices including sutures, repair devices, repair patches, slings, cardiovascular patches, orthopedic pins, attachment barriers, stents, guided tissue repair / regeneration devices, artificial cartilage repair devices, nerve guidance devices, tendon repair devices, bone marrow scaffolds, and wound dressings.

[0005] Meanwhile, Korean Patent Publication No. 10-2020-0046051 discloses a polyester with a specific PHA molecular weight and 4HB content, but it is difficult to improve adhesive properties with the disclosed configuration.

[0006] In addition, in order to impart adhesive properties to biodegradable plastics, a mixture of chemical materials is generally required, which makes biodegradation difficult and can cause environmental pollution.In addition, in order to use them as materials for absorbing and mitigating expansion / contraction, vibration, and deformation between components, like sealants, they must be given appropriate mechanical properties such as tensile strength and elongation properties in addition to adhesive properties.

[0007] Therefore, there is a demand for a biodegradable adhesive composition that is made of a single biodegradable plastic material, is environmentally friendly and biocompatible with the human body, and at the same time has adhesive properties. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Korean Patent Publication No. 10-2020-0046051 Summary of the Invention [Problem to be solved by the invention]

[0009] An object of the present invention is to provide a polyhydroxyalkanoic acid (PHA) composition which has biodegradable properties and which has improved adhesive properties as well as improved mechanical properties.

[0010] It is also an object of the present invention to provide a method for producing the PHA composition. [Means for solving the problem]

[0011] In order to solve the above problems, the present invention provides a PHA composition comprising a polyhydroxyalkanoic acid (PHA) containing 5 to 80% 3-hydroxybutyric acid (3HB) and 5 to 80% 4-hydroxybutyric acid (4HB), the PHA being poly-3-hydroxybutyric acid-co-4-hydroxybutyric acid (P3HB-4HB), the PHA having a weight average molecular weight Mw of 130,000 to 700,000 and a number average molecular weight Mn of 60,000 to 350,000.

[0012] According to an embodiment, the PHA may include two or more PHAs having different 4HB contents.

[0013] According to one embodiment, the adhesive strength of the PHA composition according to the present invention is 1 kg / in or more according to the ASTM D1876 evaluation standard.

[0014] In addition, the tensile strength according to the ASTM D638 evaluation standard is 0.1 MPa or more.

[0015] In addition, the elongation rate according to the ASTM D638 evaluation standard is 200% or more.

[0016] According to one embodiment, the composition according to the present invention is used as a sealant.

[0017] According to another embodiment of the present invention, there is provided a method for producing a PHA composition as described above.

[0018] According to an embodiment, the method of the present invention may include mixing two or more PHAs having different 4HB contents.

[0019] According to one embodiment, the method may include mixing two PHAs having different 4HB contents in a weight ratio of 10:90 to 90:10.

[0020] Further details of the embodiment of the present invention are included in the following detailed description. Effect of the Invention

[0021] According to the present invention, it is possible to provide a composition which has biodegradable properties and also has improved adhesive properties and mechanical properties.

[0022] Specifically, it is possible to provide a composition having excellent adhesive properties with plastic materials by improving adhesive properties with only biodegradable PHA without the need for additional chemicals, and it is also possible to provide a composition having improved mechanical properties such as tensile strength and elongation properties in addition to adhesive properties.

[0023] Therefore, it can be easily applied to products that require a combination of biodegradable properties, adhesive properties and mechanical properties, and can be used to manufacture products that are environmentally friendly and harmless to the human body. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] Since the present invention can be modified in various ways and has various embodiments, specific embodiments are illustrated in the drawings and described in detail in the detailed description. However, this is not intended to limit the present invention to a specific embodiment, and it should be understood that the present invention includes all modifications, equivalents, or alternatives within the spirit and technical scope of the present invention. In describing the present invention, if it is determined that a detailed description of related publicly known technology may obscure the gist of the present invention, the detailed description will be omitted.

[0025] Unless otherwise specified in the specification, the term "to" is used as an inclusive expression. For example, the term "1 to 2" does not only include 1 and 2, but also includes all numbers between 1 and 2.

[0026] In this specification, the singular expression includes the plural expression unless otherwise specified.

[0027] As used herein, the term "PHA copolymer" refers to a polymer comprised of at least two different hydroxyalkanoic acid monomers.

[0028] Hereinafter, polyhydroxyalkanoic acid (PHA) compositions and methods for preparing the same according to embodiments of the present invention will be described in more detail.

[0029] Specifically, the present invention provides a PHA composition comprising polyhydroxyalkanoic acid (PHA) containing 5-80% 3-hydroxybutyrate (3HB) and 5-80% 4-hydroxybutyrate (4HB), the PHA being poly-3-hydroxybutyrate-co-4-hydroxybutyrate (P3HB-4HB), the PHA having a weight average molecular weight Mn of 130,000-700,000 and a number average molecular weight Mn of 60,000-350,000.

[0030] According to one embodiment, the PHA may contain 5 to 80% of 3HB, for example, 5% or more, 10% or more, 20% or more, for example, 80% or less, 60% or less, 50% or less.

[0031] Furthermore, the PHA may contain 5 to 80% of 4HB, for example, 5% or more, or 10% or more, for example, 80% or less, or 70% or less, 60% or less, or 50% or less.

[0032] According to one embodiment, the weight average molecular weight of the PHA of the present invention is Mw 130,000 to 700,000, for example, Mw 130,000 or more, or Mw 150,000 or more, Mw 200,000 or more, or Mw 250,000 or more, for example, Mw 700,000 or less, or 650,000 or less.

[0033] The number average molecular weight is Mn 60,000 to 350,000, for example, Mn 60,000 or more, Mn 70,000 or more, Mn 80,000 or more, for example, Mn 350,000 or less, Mn 330,000 or less, Mn 300,000 or less.

[0034] According to an embodiment, the PHA may include two or more PHAs having different 4HB contents. Specifically, the PHA may include a PHA in which two PHAs having different 4HB contents are mixed in a weight ratio of 10:90 to 90:10, for example, 30:70 to 70:30. Specifically, the PHA may include a PHA mixture in which a PHA containing 10 g of 10% 4HB is mixed with a PHA containing 90 g of 50% 4HB.

[0035] According to one embodiment, the PHA may include a combination of crystalline PHA and amorphous PHA. For example, in the case of crystalline PHA, the 4HB content is 15% or less, and in the case of amorphous PHA, the 4HB content is 20-80%. For example, 30g of crystalline PHA polymer with a 4HB content of 10% can be mixed with 70g of amorphous PHA polymer with a 4HB content of 50%.

[0036] According to one embodiment, the PHA composition of the present invention has an adhesive strength of 1 kg / in or more, such as 1.5 kg / in or more, or 2 kg / in or more according to ASTM D1876 evaluation standard.

[0037] Furthermore, the PHA composition of the present invention has a tensile strength according to the ASTM D638 evaluation standard of 0.1 Mpa or more, for example, 0.12 Mpa or more, or 0.14 Mpa or more.

[0038] Furthermore, the PHA composition of the present invention has an elongation percentage according to the ASTM D638 evaluation standard of 200% or more, for example, 220% or more.

[0039] According to another embodiment of the present invention, there is provided a method for producing a polyhydroxyalkanoic acid (PHA) composition comprising 5-80% 3-hydroxybutyric acid (3HB) and 5-80% 4-hydroxybutyric acid (4HB), the PHA being poly-3-hydroxybutyric acid-co-4-hydroxybutyric acid (P3HB-4HB), the PHA having a weight average molecular weight Mw of 130,000-700,000 and a number average molecular weight Mn of 60,000-350,000.

[0040] According to an embodiment, the method of the present invention may include mixing two or more PHAs having different 4HB contents.

[0041] The composition according to the present invention has excellent adhesion to plastic materials, particularly to polyester-based materials. Therefore, for example, it can be manufactured into hot melt materials, hot sealing adhesive materials, etc. Furthermore, since it can improve not only adhesive properties but also mechanical properties such as tensile strength and elongation properties, it can be manufactured into sealant materials, for example, sealant film materials, etc. Unlike conventional materials such as LDPE and EVA, the composition of the present invention does not contain additives such as inorganic particles, and therefore, when additives are applied to adjust physical properties, it is possible to overcome the limitations of physical properties of conventional sealant compositions.

[0042] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention may be embodied in various different forms and should not be construed as limited to the embodiments set forth herein.

[0043] Example 1 A sheet specimen of 50 μm thickness and 10×10 cm size was prepared using a hot presser at 140° C. and 10 bar using Poly-3-hydroxybutyrate-co-50% 4-hydrobutyrate (Mw 450,000, Mn 223,000) material. That is, P3HB-co-4HB copolymer is composed of 50% 3HB monomer and 50% 4HB monomer in the total polymer structure.

[0044] The mechanical properties of the prepared specimens were measured according to the ASTM D638 tensile strength and elongation evaluation standard. To measure the adhesive strength, the sheet specimens were fixed between transparent PET films with a thickness of 50 μm, and then a 3-layered film was produced through a lamination process at 120°C, and the adhesive strength was measured according to the ASTM D1876 adhesive strength evaluation standard.

[0045] Example 2 Sheet specimens were prepared in the same manner as in Example 1, except that poly-3-hydroxybutyrate-co 50% 4-hydrobutyrate (Mw 360,000, Mn 149,000) material was used for specimen preparation.

[0046] The mechanical properties and adhesive strength of the prepared specimens were measured in the same manner as in Example 1.

[0047] Example 3 Sheet specimens were prepared in the same manner as in Example 1, except that poly-3-hydroxybutyrate-co 50% 4-hydrobutyrate (Mw 290,000, Mn 145,000) material was used for specimen preparation.

[0048] The mechanical properties and adhesive strength of the prepared specimens were measured in the same manner as in Example 1.

[0049] Example 4 Sheet specimens were prepared in the same manner as in Example 1, except that poly-3-hydroxybutyrate-co 33% 4-hydrobutyrate (Mw 400,000, Mn 160,000) material was used for specimen preparation.

[0050] The mechanical properties and adhesive strength of the prepared specimens were measured in the same manner as in Example 1.

[0051] Example 5 Sheet specimens were prepared in the same manner as in Example 1, except that poly-3-hydroxybutyrate-co 33% 4-hydrobutyrate (Mw 500,000, Mn 270,000) material was used for specimen preparation.

[0052] The mechanical properties and adhesive strength of the prepared specimens were measured in the same manner as in Example 1.

[0053] Example 6 Sheet specimens were prepared in the same manner as in Example 1, except that poly-3-hydroxybutyrate-co 33% 4-hydrobutyrate (Mw 640,000, Mn 320,000) material was used for specimen preparation.

[0054] The mechanical properties and adhesive strength of the prepared specimens were measured in the same manner as in Example 1.

[0055] Example 7 Sheet specimens were prepared in the same manner as in Example 1, except that poly-3-hydroxybutyrate-co 28% 4-hydrobutyrate (Mw 330,000, Mn 147,000) material was used for specimen preparation.

[0056] The mechanical properties and adhesive strength of the prepared specimens were measured in the same manner as in Example 1.

[0057] Example 8 Sheet specimens were prepared in the same manner as in Example 1, except that poly-3-hydroxybutyrate-co 28% 4-hydrobutyrate (Mw 550,000, Mn 220,000) material was used for specimen preparation.

[0058] The mechanical properties and adhesive strength of the prepared specimens were measured in the same manner as in Example 1.

[0059] Example 9 Sheet specimens were prepared in the same manner as in Example 1, except that poly-3-hydroxybutyrate-co 10% 4-hydrobutyrate (Mw 600,000, Mn 300,000) and poly-3-hydroxybutyrate-co 50% 4-hydrobutyrate (Mw 600,000, Mn 300,000) were compounded in a weight ratio of 3:7.

[0060] The mechanical properties and adhesive strength of the prepared specimens were measured in the same manner as in Example 1.

[0061] The results of measuring the mechanical properties and adhesive strength of Examples 1 to 9 are shown in Table 1. [Table 1]

[0062] The adhesive strength of the composition according to the present invention was confirmed to be 2 kg / in or more, which confirmed that the biodegradable plastic adhesive is also suitable for use as a sealant. Furthermore, since the above results show the physical property evaluation values ​​for the PHA composition according to the present invention alone, the physical properties can be further enhanced by adding commonly used additives.

[0063] As described above, according to the present invention, the composition of the present invention can be used alone without mixing additional chemicals to provide sufficient adhesive properties, and can be easily applied to materials that require both biodegradable properties and mechanical properties, thereby providing products that are environmentally friendly and harmless to the human body.

[0064] The above description is merely illustrative of the technical concept of the present invention, and those skilled in the art can make various modifications and variations without departing from the essential characteristics of the present invention.

[0065] Furthermore, the embodiments disclosed in the present invention are for illustrative purposes only and are not intended to limit the technical idea of ​​the present invention, and the scope of the technical idea of ​​the present invention is not limited by such embodiments. The scope of protection of the present invention should be interpreted according to the claims, and any technical idea within the scope equivalent thereto should be interpreted as being included in the scope of the rights of the present invention.

Claims

1. In polyhydroxyalkanoic acid (PHA), 3-hydroxybutyric acid (3HB) 50-95%; 5-50% 4-hydroxybutyric acid (4HB); The PHA is Poly-3-hydroxybutyrate-co-4-hydroxybutyrate (P3HB-4HB), The PHA has a weight average molecular weight Mw of 130,000 to 700,000 and a number average molecular weight Mn of 60,000 to 350,000; The PHA composition for sealants comprises two or more PHAs having different 4HB contents.

2. 2. The PHA composition for sealants according to claim 1, which has an adhesive strength of 0.39 N / mm or more according to ASTM D1876 evaluation standard.

3. The PHA composition for sealants according to claim 1, having a tensile strength of 0.1 MPa or more according to ASTM D638 evaluation standard.

4. 2. The PHA composition for sealants according to claim 1, which has an elongation of 200% or more according to ASTM D638 evaluation standard.

5. A method for producing a PHA composition for sealants, comprising producing the PHA composition for sealants according to claim 1 .

6. The method for producing a PHA composition for sealants according to claim 5, comprising mixing two or more PHAs having different 4HB contents.

7. The method for preparing a PHA composition for sealants according to claim 5, comprising mixing two PHAs having different 4HB contents in a weight ratio of 10:90 to 90:10.

Citation Information

Patent Citations

  • Production of polyester copolymer

    JP1993064591A

  • Production of hydroxyalkanoic acid copolymer

    JP1997191893A

  • PHA blend

    JP2006518799A

  • Polyester containing 4-hydroxybutyrate units

    KR1020200046051A

  • Polyhydroxy alkanoate resin composition, molded article thereof, and film or sheet

    WO2020195550A1